1995
DOI: 10.1088/0031-9155/40/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Application of glow curve analysis methods to radiotherapy mailed dosimetry with LiF TLD-100

Abstract: This paper presents the results obtained in a study of LiF TLD-100 performance for mailed dosimetry in radiotherapy, using glow curve analysis of TL evaluation and reusable chips. An excellent reusability is assured by a simple thermal treatment of 1 h at 400 degrees C followed by a controlled and reproducible cooling to room temperature that accurately reproduces the sensitivity of the detectors. Particular attention was devoted to studying sensitivity changes during room temperature storage of TLD-100 detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
2
8
1
Order By: Relevance
“…The materials used for radiation detection materials are mostly single crystal, ceramics and glass such as Al 2 O 3 :C single crystal, LiF ceramic, CaSO 4 :Dy . Glass has technological relevance in comparison with crystalline system.…”
Section: Developments In Tld Materialsmentioning
confidence: 99%
“…The materials used for radiation detection materials are mostly single crystal, ceramics and glass such as Al 2 O 3 :C single crystal, LiF ceramic, CaSO 4 :Dy . Glass has technological relevance in comparison with crystalline system.…”
Section: Developments In Tld Materialsmentioning
confidence: 99%
“…can be calculated using the Glow Curve Fitting (GCF) (Muñiz et al, 1995;Gomez-Ros et al, 2002), Whole Glow Peak (WGP) (Kalita and Chithambo, 2017), Peak Shape (PS) (Aslar et al, 2017;Keskin et al, 2018), Variable Heating Rate (VHR) (Topaksu et al, 2015;Aslar et al, 2017) and Initial Rise (IR) method (Chen and McKeever, 1997;Correcher et al, 2008), among others. The main advantage of the last method is that the E a parameter can be estimated regardless of the b value, although is a sensitive method to infer potential thermal pretreatments or changes in the heating rate.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The simple dose dependence of GR-200 is in contrast with the supralinear dependence of TLD-100. In Muñiz et al (1995) the best fit was obtained with a quadratic expression. The proportionality between TL and dose found for GR-200 is a good point in favour of this material, as calibration can be simplified requiring fewer calibration points than with TLD-100.…”
Section: Prompt Measurementsmentioning
confidence: 99%
“…around 1% (1σ ), and certainly lower than 5%. In a recent paper from our group (Muñiz et al 1995) it has been shown that using simple but carefully designed and applied TL procedures it is possible to obtain these accuracy standards with LiF:Mg,Ti (TLD-100). Glow curve analysis was employed to extract the dosimetric information contained in the TL signals, and also to study the response stability of TLD-100 in working conditions typical of a mailed system with long intervals between the three main measurement steps: dosimeter preparation, irradiation and the final evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation